Management, Empowerment, and Islamic Welfare: Evidence from Livestock Productive Waqf at Al-Azhar Institution Indonesia - Siti Zuraedah Rahmah; Wildan Munawar; Imam Abdul Aziz; Adi Rahmannur Ibnu (AL-MUZARA'AH, 2025)
Productive waqf has become a means to improve community welfare through various economic-based programs. This is inseparable from the role of waqf fund management by professional Nazir, accompanied by community empowerment. Al-Azhar Indonesia's livestock waqf program has shown good management and empowerment results, but it has not been clearly illustrated how much the influence of productive waqf management and empowerment on the welfare of mauquf 'alaih, especially measured in spiritual welfare or maqashid sharia. This study aims to prove that productive waqf management and empowerment affect the Islamic welfare through the livestock waqf program at the Al-Azhar Indonesia Institute. The research method uses descriptive quantitative methods with data collection methods through distributing questionnaires and interviews. The data analysis technique uses the Partial Least Square-Structural Equation Model (PLS-SEM) with Smart PLS software version 4. The results showed that the management and empowerment of productive waqf positively and significantly affected the Islamic welfare. The livestock waqf program run by the Al-Azhar Indonesia Institute can significantly improve material and spiritual welfare with the level of influence of management on the Islamic welfare of 0.333 or 33.3% while the level of influence of empowerment on the Islamic welfare is 0.617 or 61.7%. The level of welfare achieved during the livestock waqf program is seen in increasing income, worship, fulfilling primary needs, knowledge and skills, as well as health and education.